TDMA Based Numerical Approach on Modeling of Charge Carrier Transport and Ion Vacancy Motion in Perovskite Solar Cells - Maram, Daniyal Khosh; Abnavi, Hamed; Habibiyan, Hamidreza; Ghafoorifard, Hassan; Shekoofa, Omid (Iranian Conference on Electrical Engineering, 2020)
An important tool for explaining the hysteretic behavior in movement of electronic and ionic charges is drift-diffusion model. Adding numerical methods to these models in realistic operation situations is challenging due to the fact that some parameters have extreme values. We present a time scale dimensionless model that considers charge carrier motion and ion migration in a perovskite solar cell. The proposed model provides high accuracy accompanied by the use of realistic parameters. In order to solve matrix and equations, tridiagonal matrix algorithm (TDMA) method is exploited. Electric potential, density of ion vacancy migration, hole and electron concentration characteristics are calculated and illustrated in transient time scale. Besides, the mentioned characteristics are illustrated with different feasible built-in potential. This approach gives insight into device physics, charge transport model, ion migration and hysteresis phenomena.